PENGARUH ELEKTRONIKAL MARKETING TERHA-DAP MINAT WISATAWAN BERKUNJUNG KE PULAU SARONDE - Hasan, Ali; Hatibie, Irma Kharisma (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2014)
The purpose of the authors conducted research to determine the effectiveness of E-Marketing Interests Against Tourist Visits in Gorontalo Saronde Island and can be beneficial for the institutions, the object of research, author and upcoming research. Location of the researched, is Saronde Island in Gorontalo. E-Marketing is one of the factors that play an important role in running a marketing business. E marketing or Electronic Marketing is one of the breakthroughs that are quite reliable in marketing a tourism product. Saronde Island as one of the tourist attraction managed by GAB (Natural Gorontalo Maritime) uses the concept of E Marketing as one way powerful enough to market their products. This research uses quantitative, the measurement data in the form of numbers. Variables examined include facebook marketing, email marketing, web marketing and blackberry messenger marketing. The number of samples from total sample is 60 respondents to the normality test, autocorrelation test results and test multikolinear data formula that relies on the analysis of the results of Durbin Watson and VIF (Variance Inflation Factor). With the technique of multiple regression analysis. The analysis result showed Blackberry Massenger is most effective changer variable, which conducted to influent visiting of tourist, than others variable. The results showed a significant effect on interest visiting of tourists at Saronde island of Gorontalo. The implications of this study, is to be helpful to the reader, or for anyone who wants to continue the same thing in future research. Hypothesis Testing depend variable to independent variable, the probability value is < 0.01. Keywords: E-Marketing, Interests For Visit, Facebook, Email, Weblogs, Blackberry Massenger, Tourist